Deviant knowledge : criminology, politics, and policy - Walters, Reece (Willan, 2003)
In 'Deviant Knowledge' Reece Walters examines the politics of criminology and the ways in which criminological knowledge is generated. It includes an overview of the politics and practice of conducting criminological research and the ways that regulatory and governing authorities set research agendas.